Hubungan Tingkat Stres Dengan Kadar Gula Darah Sewaktu Pada Mahasiswa Kedokteran UPN “Veteran” Jakarta - Nabillah Faradita Hasan; Retno Widowati; Suprihatin (Jurnal Analis Kesehatan, 2025)
Academic stress refers to mental and emotional pressure arising from educational demands, commonly experienced by students, especially medical students due to their complex academic workload. Prolonged stress can trigger an increase in cortisol levels, which promotes glucose release into the bloodstream, potentially raising blood sugar levels. This study aimed to examine the relationship between academic stress levels and random blood glucose levels among medical students at Universitas Pembangunan Nasional “Veteran” Jakarta as an early effort to detect the risk of prediabetes. A cross-sectional design was used with 70 respondents. Academic stress levels were measured using a Heart Rate Variability Analyzer, while random blood glucose levels were assessed using a gluco test strip. Results showed that all respondents had normal blood glucose levels, with varying stress levels: 30.0% were categorized as excellent and 12.9% as bad. Spearman correlation test indicated no significant relationship between academic stress and random blood glucose levels (p = 0.134; r = 0.181). These findings suggest that the absence of a significant correlation may be influenced by the respondents' young age and optimal metabolic condition, which could mitigate the physiological impact of stress on blood glucose levels.